2005
DOI: 10.2188/jea.15.173
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Risk of All-cause Mortality: The Jichi Medical School (JMS) Cohort Study

Abstract: BACKGROUND: There have been comparatively few large-scale cohort studies analyzing all-cause mortality due to cigarette smoking. The goal of this analysis is to investigate the relationship between smoking status and all-cause mortality, and to evaluate the effect of smoking in the Japanese. METHODS: The baseline data were collected between 1992 and 1995. Ultimately, 10,873 Japanese (4,280 males and 6,593 females) aged 19 years or older from 12 rural communities located across Japan participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Current smokers in ANZ had twice the risk compared with never smokers, whereas in Asia, current smokers had a one-third higher risk. The magnitude of these estimates, as well as the smaller observed effect among Asian cohorts, are consistent with previous findings from studies conducted in Australia,10 New Zealand11 and Europe1 1214 China,1518 Taiwan,19 20 Japan2123 and Korea 24…”
Section: Discussionsupporting
confidence: 91%
“…Current smokers in ANZ had twice the risk compared with never smokers, whereas in Asia, current smokers had a one-third higher risk. The magnitude of these estimates, as well as the smaller observed effect among Asian cohorts, are consistent with previous findings from studies conducted in Australia,10 New Zealand11 and Europe1 1214 China,1518 Taiwan,19 20 Japan2123 and Korea 24…”
Section: Discussionsupporting
confidence: 91%
“…These values were similar to those of Iso et al (10), who found that 23.5% and 6.0% of CVD mortality could be explained by smoking status. Other Japanese studies have also reported similar values for the PAF for all-cause mortality (18)(19)(20) due to smoking (range of PAF: 22-34% for men and 0-5% for women), and other Asian studies have yielded PAFs that are comparable to those in Japan (8).…”
Section: Discussionsupporting
confidence: 55%
“…Despite its importance as a measure in the implementation of disease prevention programs and health policies, few studies to date have assessed PAR. A cohort study in Japan [5] reported 24.9% of male deaths due to all causes. The results from a cohort in Taiwan [7] showed a PAR% of 13.9% for all causes of death, 59.3% for lung cancer, and 30.2% for ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Relative risk is a measure of the strength of an association, and is an indicator used to assess the possibility of a causal relationship. In contrast, relatively few studies use population attributable risk (PAR) [5][6][7], an important measurement of public health impact and health policy decision making.…”
Section: Introductionmentioning
confidence: 99%